Le contrat sexuel - Pateman, Carole (La Découverte Poche, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »-- Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences